1981
DOI: 10.1111/j.1348-0421.1981.tb00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Transformed Phenotypes in Sheep Fibroblasts by Culture Fluids from Cells Persistently Infected with Bovine Leukemia Virus

Abstract: FLK cells are fetal lamb kidney cells persistently infected with bovine leukemia virus (BLV). 3178 cells, originating from calf-form bovine lymphosarcoma, also showed persistent production of BLV and alteration of cell morphology after treatment with 5'-iodo-2'-deoxyuridine. In the present paper, the first in vitro transformation of sheep fibroblasts by inoculation with BLV materials from these two cell lines is described. In a few passages after inoculation with these viral materials, morphological alteration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1982
1982
1987
1987

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Bovine leukemia virus (BLV) is a unique retrovirus which causes naturally occurring lymphosarcom~ in cattle. Although BLV is competent for replication, it is able to transform sheep fibrobtasts in vitro (5,6). Previous analysis by using polyclonM antibody, showed that the transformed sheep fibroblasts (SF-28 cells) expressed new antigen(s) which differed from BLV structural proteins (gp51 and p24) and might be associated to transformation (5).…”
Section: Discussionmentioning
confidence: 98%
“…Bovine leukemia virus (BLV) is a unique retrovirus which causes naturally occurring lymphosarcom~ in cattle. Although BLV is competent for replication, it is able to transform sheep fibrobtasts in vitro (5,6). Previous analysis by using polyclonM antibody, showed that the transformed sheep fibroblasts (SF-28 cells) expressed new antigen(s) which differed from BLV structural proteins (gp51 and p24) and might be associated to transformation (5).…”
Section: Discussionmentioning
confidence: 98%
“…However, little or no successful in vitro transformation of sheep and calf cells by BLV has been reported. Onuma et al (1981) reported the induction of transformed phenotypes in sheep fibroblasts from testes following inoculation with BLV, but cells infected with BLV became transformed only after several passages. We describe herein the rapid successful transformation of fetal lamb kidney (FLK) cells by BLV.…”
mentioning
confidence: 97%
“…Thus, the mechanism of the cellular transformation by BLV still remains enigmatic. However, the presence of a BLV provirus in all the leukemic cells (1) and the ability of BLV to transform cells in vitro (9,10) suggest that the BLV genome possesses a possible transforming gene. Recent molecular biological (16) and biochemical (14) studies suggest that the BLV genome harbors the .unique XBL gene encoding a non-structural 38 kDa protein, corresponding to the X gene of HTLV (16,17).…”
mentioning
confidence: 99%